Long-term upregulation of cortical glutamatergic AMPA receptors in a mouse model of chronic visceral pain. Issue 1 (December 2015) - Liu, Shui-Bing; Zhang, Ming-Ming; Cheng, Lin-Feng; Shi, Jiao; Lu, Jing-Shan; Zhuo, Min
Abstract Background Irritable bowel syndrome (IBS) is one of the most common functional gastrointestinal disorders and it causes long-lasting visceral pain and discomfort. AMPA receptor mediated long-term potentiation (LTP) has been shown to play a critical role in animal models of neuropathic and inflammatory pain. No report is available for central changes in the ACC of mice with chronic visceral pain. Results In this study, we used integrative methods to investigate potential central plastic changes in the anterior cingulate cortex (ACC) of a visceral pain mouse model induced by intracolonic injection of zymosan. We found that visceral pain induced an increased expression of AMPA receptors (at the post synapses) in the ACC via an enhanced trafficking of the AMPA receptors to the membrane. Both GluA1 and GluA2/3 subunits were significantly increased. Supporting biochemical changes, excitatory synaptic transmission in the ACC were also significantly enhanced. Microinjection of AMPA receptor inhibitor IEM1460 into the ACC inhibited visceral and spontaneous pain behaviors. Furthermore, we found that the phosphorylation of GluA1 at the Ser845 site was increased, suggesting that GluA1 phosphorylation may contribute to AMPA receptor trafficking. Using genetically knockout mice lacking calcium-calmodulin stimulated adenylyl cyclase subtype 1 (AC1), we found that AMPA receptor phosphorylation and its membrane trafficking induced by zymosan injection were completely blocked. Conclusions Our results provide direct evidence for cortical AMPA receptors to contribute to zymosan-induced visceral and spontaneous pain and inhibition of AC1 activity may help to reduce chronic visceral pain.